Enrolled, yet Absent: Children with Disabilities - Mehdi, Jayita (Voices of Teachers and Teacher Educators, 2020)
This paper discusses about absenteeism of children from schools. It focuses primarily on the issues faced by the children with disabilities and their families. It also briefly discusses the factors affecting the school attendance of such children. The concluding section discusses the measures that can be taken to limit absenteeism of children with disabilities from school.